Quick-setting high-strength expansive type leakage crack plugging material and method and application of rapid-setting high-strength expansive type leakage crack plugging material
Through scientific and reasonable material ratio and compounding technology, a fast-condensing high-strength expansion leakage crack sealing material was prepared, which solved the problems of complex preparation of existing materials, easy to layer flocculation and shrinkage defects, and achieved rapid coagulation, shrinkage resistance, micro-expansion, high strength and durability sealing effect.
Patent Information
- Application Number
- CN202510036227.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-09
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2045-01-09
AI Technical Summary
The existing fast-coagulation sealing materials have problems such as complex preparation and easy to layer flocculate and shrinkage defects, resulting in unsatisfactory sealing effect.
The basic material formed by combining ordinary silicate cement, desulfurization gypsum, calcium oxide, alkaline alumina, calcium formate, hydrated calcium silicate, carboxy cellulose and solid polycarboxylic acid water reducer is used to combine the active components of polymeric aluminum sulfate, magnesium sulfate, disodium ethylenediaminetetraacetate, borax and defoaming agent, as well as the control components of ultrafine fly ash, ultrafine silica, ultrafine hydroxyapatite, ultrafine zinc sulfate, nanotitanium dioxide and ultrafine boron nitride, and the control components of rapid settling high-strength expansion leakage crack sealing material is prepared through mixed compounding technology.
The rapid condensation, shrinkage resistance, micro-expansion, high strength and durability of the material are achieved, ensuring the stability and durability of the sealing effect.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of cement-based material admixtures, and in particular relates to a quick-setting high-strength expansion type leakage crack plugging material, a method and an application thereof. Background Art
[0002] In the process of coal mining, a large number of goafs will be generated, and problems such as water gushing, water seepage and gas accumulation will occur due to cracks and voids around the mining areas. Therefore, in the process of coal mining, the main measures to eliminate accidents such as mine water seepage, water leakage, collapse and gas explosion are to seal the water gushing cracks in the coal rock strata around the goafs, seal the water seepage cracks in the tunnels and seal the gas extraction holes with grouting. In order to effectively seal these cracks and voids and eliminate problems such as water seepage, water leakage and gas leakage, the materials used for crack sealing and pore filling must have the characteristics of rapid solidification (quick setting), micro-expansion in volume, anti-permeability, high strength and durability. At present, the quick-setting plugging materials used for plugging water-permeable cracks in the coal mining process include organic polymer plugging materials, silicate-modified organic polymer plugging materials and inorganic plugging materials. Organic polymer quick-setting plugging materials mainly include polyurethane, phenolic resin, epoxy resin, etc. Their advantages are good fluidity, good plugging effect, high strength, high toughness and the ability to bond coal and rock; their disadvantages are complicated preparation process, relatively high price, spontaneous combustion and large heat release during solidification, which may ignite coal. Inorganic quick-setting plugging materials are mainly inorganic composites formed by ordinary silicate cement and sulphoaluminate cement, aluminum sulfate, calcium oxide, sodium aluminate, calcium sulfate, etc., which are characterized by simple preparation, low price, fast setting speed, low solidification temperature, flame retardant, good stability, etc. The disadvantages are easy shrinkage and poor durability. Due to the above advantages of inorganic quick-setting plugging materials, the current and future development trend of coal mine crack plugging quick-setting materials is inorganic quick-setting plugging materials. The main problems that need to be solved are problems in early strength, volume shrinkage and durability. At present, inorganic quick-setting materials mainly add quick-setting agents to cement matrix. During grouting, cement-based materials and quick-setting agents are mixed together and injected into the parts that need to be plugged and filled to make them set quickly. Therefore, quick-setting agents are the core and focus of current plugging and filling materials. Quick-setting agents mainly include powder quick-setting agents and liquid quick-setting agents. During the construction process, powder quick-setting agents have problems such as large amount of dust and large loss of strength in the later stage, which leads to their gradual replacement by liquid quick-setting agents. Liquid quick-setting agents can be divided into alkali-containing and alkali-free liquid quick-setting agents according to the alkali content. Alkali liquid quick-setting agents mainly include metaaluminate type, sodium silicate type and sulfate type liquid quick-setting agents. Alkali liquid quick-setting agents have the advantages of low dust content and small dosage, but due to the high alkali content, the retention rate of concrete's 28-day compressive strength is low. Alkali-free liquid quick-setting agents are mainly aluminum sulfate type liquid quick-setting agents, which are made with aluminum sulfate as the main accelerating component and supplemented with other components. Aluminum sulfate type alkali-free liquid accelerator avoids the disadvantages of alkali liquid accelerator causing large strength loss of concrete in the later stage and alkali-aggregate reaction, and is non-corrosive and environmentally friendly. Therefore, alkali-free liquid accelerator is the focus of current research and future development and application.However, there are still some urgent problems to be solved in alkali-free liquid accelerators, such as large dosage, high cost, poor stability, susceptibility to flocculation, precipitation, crystallization and other phenomena, and poor adaptability to different cements. These defects limit its promotion and application.
[0003] Inorganic alkali-free liquid accelerators are currently a hot topic of research, and the focus of the research is on the stability and application effect of alkali-free liquid accelerators. Chen Yansheng et al. used sodium oxalate, aluminum hydroxide, hydrofluoric acid, aluminum sulfate, ethanolamine, diethanolamine, etc. to react to prepare an alkali-free liquid accelerator. When the dosage was 6% of cement, its initial and final setting times were 134 seconds and 390 seconds, respectively, and the compressive strengths of 1 day and 28 days were 10.6MPa and 98.5MPa, respectively. The accelerator has the characteristics of small dosage, low cost, good stability, no flocculation, precipitation, crystallization, simple preparation process, good adaptability and coagulation effect (Chen Yansheng, Zhang Yun, Wei Kai, et al., Preparation and application research of highly adaptable alkali-free liquid accelerator, New Building Materials, 2022, (7): 122-127). Li Chongzhi et al. prepared diethanolamine carboxylate silica gel complex stabilizer using diethanolamine and oxalic acid under the catalysis of concentrated sulfuric acid, and then reacted with aluminum sulfate, diethanolamine and magnesium sulfate to prepare alkali-free liquid accelerator. When the dosage was 8% of cement mass, the initial setting time was 200 seconds, the final setting time was 495 seconds, the 6-hour compressive strength was 1.2 MPa, the 1-day compressive strength was 13.5 MPa, and the 28-day compressive strength was 46.3 MPa. It overcomes the problems of poor stability, slow hardening speed and poor compatibility with cement of traditional liquid alkali-free accelerator (Li Chongzhi, Deng Songwen, Dong Peng, et al., Research and Application of High-performance Alkali-free Liquid Accelerator, New Building Materials, 2023, (3): 59-62). Deng Lin et al. prepared alkali-free liquid accelerator by reacting industrial titanium dioxide waste acid, hydrofluoric acid and aluminum hydroxide. When the dosage is 7%, the initial setting time and final setting time are 190 seconds and 320 seconds respectively, the compressive strength in 1 day is 11.2 MPa, and the compressive strength in 28 days is 48.5 MPa. The accelerator has the characteristics of fast setting time, low dosage and high strength (Deng Lin, Mao Xuehua, Study on the performance and hydration mechanism of aluminum sulfate type alkali-free accelerator prepared from industrial titanium dioxide waste acid, 2022, 42 (11): 211-216). Zhang Guoli et al. prepared highly active aluminum hydroxide with aluminum sulfate and ammonia water, and then reacted with aluminum sulfate, oxalic acid and triethanolamine to prepare polyaluminum sulfate, and then compounded with sodium fluorosilicate, calcium formate and EDTA to prepare liquid alkali-free accelerator. When the dosage is 5%, the initial setting time is 200 seconds, the final setting time is 380 seconds, the strength in 1 day is 7.3 MPa, and the strength in 28 days is 43.5 MPa. The shortcomings of aluminum sulfate type accelerator, such as poor stability, flocculation, stratification, and precipitation, which lead to uneven mixing of concrete, different setting times, and poor strength and durability, have been overcome. (Zhang Guoli, Wu Zhihong, Deng Yue, et al., Preparation and stability of ethylenediaminetetraacetic acid (EDTA) modified aluminum sulfate alkali-free liquid accelerator, Journal of Materials Science and Engineering, 2022, 40 (3): 466-473).Liang Hui et al. prepared a liquid alkali-free accelerating agent by reacting aluminum sulfate, magnesium sulfate, diethanol, monoisopropanolamine, fluorosilicic acid and glycolic acid. When the dosage was 6%, the benchmark cement could be initially set in 210 seconds and finally set in 565 seconds. The compressive strength in 1 day reached 11.5 MPa and the compressive strength in 28 days reached 48.6 MPa. The accelerating agent has Al. 3+It has the advantages of high content, good stability, good reinforcement effect, and green, environmentally friendly and safe (Liang Hui, Liao Wenjie, Long Caixia, et al., Preparation and performance research of liquid alkali-free accelerator, New Building Materials, 2023, (3): 138-139). Wu Wenxian used ammonium acryloyl, ammonium persulfate, acrylic acid, thioglycolic acid and potassium hydrogen tartrate to prepare a suspension stabilizer; ethylenediaminetetraacetic acid, triethanolamine, p-toluenesulfonic acid and hydroquinone were used to react to prepare a complexing enhancer; and then the prepared suspension stabilizer, complexing enhancer, aluminum sulfate, hydroxymethyl cellulose and oxalic acid were compounded to prepare a new type of alkali-free liquid accelerator. It solves the problems of poor stability, low strength and prominent compatibility with cement of the accelerator. (Wu Wenxian, Development of a new type of alkali-free liquid accelerator, New Building Materials, 2022, (6): 124-129). Song Shaofei et al. prepared a fluorine-free and alkali-free liquid accelerator using aluminum sulfate, modified triethanolamine, citric acid, disodium EDTA, phosphoric acid, glycerol, ferrous sulfate, and sodium carbonate. When the solid content was 2.8%, the initial setting time was 147 seconds, the final setting time was 390 seconds, and the one-day compressive strength was 9.67 MPa. It has the advantages of low content, short setting time, and low cost (Song Shaofei, Qu Qiheng, Li Wenli, et al., Preparation and performance study of new fluorine-free and alkali-free liquid accelerator, New Building Materials, 2023, (3): 139-142). Deng Songwen prepared a liquid high-performance alkali-free liquid accelerator using aluminum sulfate, oxalic acid, diethanolamine, magnesium sulfate, fumed silica, etc. When the dosage was 8%, the cement paste had an initial setting of 144 seconds and a final setting of 282 seconds. The 6h compressive strength of the cement was 1.3MPa, the 1-day compressive strength was 13.4MPa, and the 28-day compressive strength was 49.2MPa. It has the characteristics of low alkali content, high early strength and good adaptability (Deng Songwen, Research and Application of High-Performance Alkali-Free Liquid Accelerator for Tunnels, Master's Thesis of Beijing University of Civil Engineering, 2023). Liu Yuan et al. prepared aluminum formate from formic acid and aluminum hydroxide, and then heated it with fluorosilicic acid, triethanolamine, hydroxyapatite, and aluminum sulfate to obtain an alkali-free liquid accelerator. When the dosage is 8%, the initial setting time is 159 seconds, the final setting time is 333 seconds, the compressive strength is 13.2 MPa at 1 day, 49.6 MPa at 28 days, and 53.5 MPa at 90 days. Introducing aluminum formate into alkali-free liquid accelerator can reduce the sulfate content in the accelerator, reduce the adverse effects on the durability of concrete, shorten the initial setting time and final setting time of cement, and significantly enhance the early and late strength of cement (Liu Yuan, Zhu Fangfang, Zhang Yuanyong, et al., Effect of aluminum formate modified aluminum sulfate-based alkali-free liquid accelerator on cement properties, Bulletin of the Chinese Ceramic Society, 2024, 43 (12): 4331-4339). Zhang Xuhua et al. used formic acid to react with aluminum sulfate and diethanolamine and added magnesium nitrate to obtain an alkali-free liquid accelerating agent. At an 8% dosage, the initial and final setting times of the cement mortar were 276 seconds and 492 seconds, respectively. The compressive strength of the cement mortar could reach 20.23 MPa in one day and 49.6 MPa in 28 days.This accelerator has good temperature adaptability and admixture compatibility. It can still play a good accelerating effect when working in synergy with naphthalene / polycarboxylic acid water reducers. A small amount of Mg is introduced into the accelerator. 2+ , which can combine with OH- produced by cement hydration to generate Mg(OH) 2 , which has a certain inhibitory effect on the volume shrinkage of cured cement mortar; among them, Al 3+ and SO 4 2- It can induce a large amount of calcium aluminate crystal deposition in the early stage of the hydration reaction to form a spatial network structure, which promotes the rapid solidification of cement slurry (Zhang Xuhua, Tian Mingkun, Zhang Gaoyin, et al., Synthesis and performance evaluation of aluminum sulfate type alkali-free accelerating agent, China Building Materials Science and Technology, 2024, 33 (4): 21-24).
[0004] Through the analysis of the research and application status of quick-setting plugging and filling materials for cracks and pores in coal mines in recent years, it is found that there are the following problems: (1) The current research and application are mainly inorganic plugging and filling materials with silicate cement as the main component. The quick-setting effect is mainly achieved by adding liquid inorganic alkali-free quick-setting agent. During the construction process, the quick-setting agent needs to be added during grouting; (2) The quick-setting agent is mainly composed of aluminum sulfate, which reacts with other components such as ethanolamine, diethanolamine, triethanolamine, oxalic acid, glycerol, etc. The preparation process of the quick-setting agent is complicated and troublesome; (3) The quick-setting agent is in liquid form, and its transportation and storage are relatively troublesome. During the storage process, the liquid quick-setting agent itself is prone to stratification, flocculation and precipitation, which affects the use effect; (4) The main problem of the current crack plugging and filling materials is the shrinkage defect, which makes the plugging and filling bodies easy to fall off at the cracks. Summary of the invention
[0005] In order to overcome the shortcomings of the above-mentioned prior art, the purpose of the present invention is to provide a fast-setting, high-strength expansive leakage crack plugging material, method and application, so as to solve the technical problems of complex preparation, easy stratification flocculation and shrinkage defects in the existing fast-setting plugging materials, and achieve a plugging effect of rapid setting, anti-shrinkage micro-expansion, high strength and durability.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions: The invention discloses a method for preparing a quick-setting high-strength expansion type leakage crack plugging material, comprising the following steps: Step 1, mixing cement, desulfurized gypsum, calcium oxide, basic alumina, calcium formate, hydrated calcium silicate, carboxyl cellulose and solid polycarboxylate water reducer to obtain component A; Step 2, mixing polyaluminium sulfate, magnesium sulfate, disodium ethylenediaminetetraacetate, borax and a defoamer to obtain component B; Step 3, mixing ultrafine fly ash, ultrafine silicon dioxide, ultrafine hydroxyapatite, ultrafine zinc sulfate, nano titanium dioxide and ultrafine boron nitride to obtain component C; Step 4, mix component A with water, stir evenly to obtain component A slurry; mix component B with water, stir evenly to obtain component B slurry; mix component C with water, stir evenly to obtain component C slurry; mix component A slurry, component B slurry and component C slurry evenly, then add an activator, stir evenly, and obtain a fast-setting high-strength expansion type leakage crack plugging material.
[0007] Preferably, in step 4, the mass ratio of component A, component B, component C and activator is (186.6-237.8): (51.6-68.9): (120-153): (6-9); According to the mass percentage, the component A slurry is prepared by adding 75-95 parts of water to 186.6-237.8 parts of component A and stirring evenly; the component B slurry is prepared by adding 21-28 parts of water to 51.6-68.9 parts of component B and stirring evenly; the component C slurry is prepared by adding 48-61.2 parts of water to 120-153 parts of component C and stirring evenly; The activator is aluminum carbonate powder with a purity of 98%.
[0008] Preferably, in step 1, the mass ratio of cement, desulfurized gypsum, calcium oxide, basic alumina, calcium formate, calcium silicate hydrate, carboxyl cellulose and solid polycarboxylate water reducer is (85-95): (45-55): (20-30): (15-25): (10-15): (10-15): (0.1-0.3): (1.5-2.5); In step 2, the mass ratio of polyaluminium sulfate, magnesium sulfate, disodium ethylenediaminetetraacetate, borax and defoamer is (40-50): (10-15): (0.5-0.6): (1-3): (0.1-0.3); In step 3, the mass ratio of ultrafine fly ash, ultrafine silicon dioxide, ultrafine hydroxyapatite, ultrafine zinc sulfate, nano titanium dioxide and ultrafine boron nitride is (40-50): (30-35): (25-30): (10-15): (5-8): (10-15).
[0009] Preferably, in step 1, the cement is ordinary Portland cement P·O 42.5; the main component of desulfurized gypsum is CaSO 4 ·2H 2 O, its content is 93% and the average particle size is 50μm.
[0010] Preferably, in step 1, calcium oxide, basic alumina, calcium formate, calcium silicate hydrate, carboxyl cellulose and solid polycarboxylate water reducer are all powdered materials with a purity greater than 99%.
[0011] Preferably, in step 2, polyaluminum sulfate, magnesium sulfate, disodium ethylenediaminetetraacetate and borax are all powdered materials with a purity greater than 98%; and the defoaming agent is a solid silicone defoaming agent with a purity of 99%.
[0012] Preferably, in step 3, the particle size of the ultrafine fly ash is 0.4-0.6 μm, the loss on ignition is not more than 3.2%, the water requirement is not more than 91%, the water content is not more than 0.2%, and the activity index is 85%-90%.
[0013] Preferably, in step 3, the purity of ultrafine silicon dioxide, ultrafine hydroxyapatite, ultrafine zinc sulfate and ultrafine boron nitride is greater than 99%, and the particle size is 1-5 μm; the particle size of nano titanium dioxide is 30-50 nm.
[0014] The invention also discloses a quick-setting high-strength expansive leakage crack plugging material, which is prepared by the preparation method of the quick-setting high-strength expansive leakage crack plugging material; the quick-setting high-strength expansive leakage crack plugging material has an initial setting time of 2-3 minutes and a final setting time of 4-6 minutes; a 1-hour compressive strength of 7.55-7.93 MPa; a 1-day compressive strength of 26.54-31.52 MPa; a 28-day compressive strength of 53.46-56.62 MPa; a 90-day compressive strength of 58.81-63.68 MPa; a 28-day carbonization resistance depth of 0.1-0.2 mm; and a 28-day volume shrinkage rate of 0.1%-0.11%.
[0015] The invention also discloses the application of the quick-setting high-strength expansive leakage crack plugging material prepared by the preparation method of the quick-setting high-strength expansive leakage crack plugging material in water and gas leakage, gap plugging and void filling and repairing in coal mines, tunnels and dams.
[0016] Compared with the prior art, the present invention has the following beneficial effects: The invention discloses a method for preparing a fast-setting high-strength expansive leakage crack plugging material. The fast-setting high-strength expansive leakage crack plugging material is composed of three material systems with different effects and functions, namely, a basic material component formed by compounding ordinary silicate cement, desulfurized gypsum, calcium oxide, alkaline aluminum oxide, calcium formate, hydrated calcium silicate, carboxyl cellulose and solid polycarboxylic acid water reducer; an active component formed by compounding polyaluminum sulfate, magnesium sulfate, disodium ethylenediaminetetraacetic acid, borax and a defoamer, which mainly functions to accelerate the hydration reaction speed and coagulation speed of the basic material to achieve a rapid coagulation effect; and a material system formed by ultrafine fly ash, ultrafine silicon dioxide, ultrafine hydroxyapatite, ultrafine zinc sulfate, nano titanium dioxide and ultrafine boron nitride, which can regulate the hydration product and microstructure and macrostructure of the solidified material and has good heat conduction function, so that the solidified material structure has the characteristics of being dense, shrinkage-resistant and micro-expansion-resistant, and realizing high-strength embedded locking plugging of leakage cracks and gaps, and achieving permanent plugging and filling effects. In terms of the preparation method, the three functional components are all compound components formed by the method of mixing and compounding the selected materials, and do not need to be prepared by heating and long-term chemical reaction. In terms of the application method, the three components are mixed with water and then mixed with an activator and injected into cracks and gaps, and then mixed and grouting is quickly solidified and formed, and the curing process releases little heat and has a low temperature. The structure of the formed plugging and filling materials is uniform, resistant to shrinkage, slightly expanded, high in early strength, good in later durability, and the formed plugging and filling effects are good. The quick-setting high-strength expansion type leakage crack plugging material prepared by the present invention has a scientific and reasonable composition, clear material functions, simple and easy preparation method, simple and convenient packaging, transportation and storage, no heating is required in the preparation process, low energy consumption, green and environmentally friendly, obvious plugging and filling effects, initial setting time of 2~3min, final setting time of 4~6min, 1-hour compressive strength greater than 7MPa, 1-day compressive strength greater than 25MPa, and 28-day strength greater than 50MPa.
[0017] The present invention also discloses a quick-setting high-strength expansion type leakage crack plugging material obtained by the above-mentioned preparation method, which is composed of three parts, namely, a basic material with cement-based materials as the main component, a quick-setting accelerator constituting a coagulation-promoting component, and a component with anti-shrinkage micro-expansion and micro-structure regulation and heat conduction. The whole material is formed by mixing and compounding, and the preparation process does not have heating and chemical reaction processes, and has the effects of low energy consumption and green environmental protection. The quick-setting high-strength expansion type leakage crack plugging material has a uniform and dense structure, excellent anti-shrinkage performance, and significant micro-expansion characteristics. It can maintain a stable form during the curing process, effectively resist the influence of external stress, and is not easy to crack or deform. It not only has the rapid coagulation characteristics of 2 to 3 minutes initial coagulation and 4 to 6 minutes final coagulation, but also has high early strength, and the compressive strength can reach 7.55 to 7.93 MPa in 1 hour, and the compressive strength in 1 day is as high as 26.54 to 31.52 MPa, which fully meets the performance requirements of water gushing, water permeability and gas plugging materials. At the same time, the compressive strength reached 53.46~56.62 MPa in 28 days, and it was enhanced to 58.81~63.68 MPa in 90 days, showing excellent subsequent enhancement. It also has good durability. The results of the 28-day freeze-thaw test and the anti-permeability test show that it has excellent anti-freeze performance, the carbonization depth is only 0.1~0.2 mm, and the 28-day volume shrinkage rate is controlled at 0.1%~0.11%, showing excellent volume stability. More importantly, the results of the 28-day and 90-day shrinkage tests show that the material has excellent anti-shrinkage and micro-expansion effects. The early strength is extremely high and the later durability is excellent. It can reach the required strength standard in a very short time and meet the strict requirements of the project for material performance. The initial setting time and final setting time are very short, which greatly improves the construction efficiency, shortens the construction period, and reduces the project cost. The plugging and filling effects are very obvious, providing a solid and reliable guarantee for the project.
[0018] The present invention also discloses the application of the quick-setting high-strength expansion type leakage crack plugging material prepared by the above-mentioned preparation method in water vapor leakage, gap plugging and gap filling and repairing of coal mines, tunnels and dams. Since the quick-setting high-strength expansion type leakage crack plugging material has an extremely high embedded locking plugging ability, it can effectively prevent the generation of water vapor leakage cracks, greatly improving the safety and durability of the project. Its dense microstructure and excellent anti-shrinkage micro-expansion performance make the structure after plugging more stable and reliable, and can withstand the test of various external environments for a long time. At the same time, the quick-setting high-strength expansion type leakage crack plugging material is convenient and fast to construct, can be quickly solidified and formed, greatly shortens the construction period, and improves the project efficiency. In addition, the quick-setting high-strength expansion type leakage crack plugging material also has good adaptability and compatibility, can be perfectly combined with various engineering materials and structures, and provides a strong guarantee for the overall performance and stability of the project. Therefore, this fast-setting, high-strength expansion-type leakage crack plugging material has significant advantages and broad application prospects in plugging water and gas leakage gaps and filling and repairing gaps in coal mines, tunnels, dams and other projects. DETAILED DESCRIPTION
[0019] The technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0020] In the present invention, unless otherwise specified, all the embodiments and preferred implementation methods mentioned herein can be combined with each other to form a new technical solution.
[0021] In the present invention, unless otherwise specified, all technical features and preferred features mentioned herein can be combined with each other to form a new technical solution.
[0022] In the present invention, unless otherwise specified, percentage (%) or part refers to the weight percentage or weight part relative to the composition.
[0023] In the present invention, unless otherwise specified, the components or preferred components involved can be combined with each other to form a new technical solution.
[0024] In the present invention, unless otherwise specified, the numerical range "a~b" represents an abbreviation of any real number combination between a and b, where a and b are real numbers. For example, the numerical range "6~22" means that all real numbers between "6~22" have been listed in this document, and "6~22" is just an abbreviation of these numerical combinations.
[0025] The “range” disclosed in the present invention is in the form of a lower limit and an upper limit, which can be one or more lower limits, and one or more upper limits, respectively.
[0026] In the present invention, the term "and / or" used herein refers to any combination and all possible combinations of one or more of the associated listed items, and includes these combinations.
[0027] In the present invention, unless otherwise specified, each reaction or operation step can be carried out sequentially or in accordance with the sequence. Preferably, the reaction method herein is carried out sequentially.
[0028] Unless otherwise specified, the professional and scientific terms used herein have the same meanings as those familiar to those skilled in the art. In addition, any method or material similar or equivalent to the described content may also be applied to the present invention.
[0029] The present invention provides a method for preparing a quick-setting high-strength expansion type leakage crack plugging material, comprising the following steps: Step 1: 85-95 parts of cement, 45-55 parts of desulfurized gypsum, 20-30 parts of calcium oxide, 15-25 parts of basic alumina, 10-15 parts of calcium formate, 10-15 parts of hydrated calcium silicate, 0.1-0.3 parts of carboxyl cellulose and 1.5-2.5 parts of solid polycarboxylate water reducer are mixed uniformly according to the weight ratio to obtain component A; Step 2, according to the mass parts, 40-50 parts of polyaluminium sulfate, 10-15 parts of magnesium sulfate, 0.5-0.6 parts of disodium ethylenediaminetetraacetate, 1-3 parts of borax and 0.1-0.3 parts of defoamer are mixed uniformly to obtain component B; Step 3, according to the mass parts, 40-50 parts of ultrafine fly ash, 30-35 parts of ultrafine silicon dioxide, 25-30 parts of ultrafine hydroxyapatite, 10-15 parts of ultrafine zinc sulfate, 5-8 parts of nano titanium dioxide and 10-15 parts of ultrafine boron nitride are mixed uniformly to obtain component C; Step 4: Add 75-95 parts of water to 186.6-237.8 parts of component A, stir evenly to obtain component A slurry; add 21-28 parts of water to 51.6-68.9 parts of component B, stir evenly to obtain component B slurry; add 48-61.2 parts of water to 120-153 parts of component C, stir evenly to obtain component C slurry. Mix the component A slurry, component B slurry and component C slurry evenly, add an activator, stir evenly, and obtain a fast-setting high-strength expansion type leakage crack plugging material, which is immediately injected into the leakage and gaps that need to be plugged.
[0030] Furthermore, in step 1, the cement is labeled as ordinary Portland cement P·O 42.5.
[0031] Furthermore, in step 1, the main component of desulfurized gypsum is CaSO 4 ·2H 2 O, its content is 93% and the average particle size is 50μm.
[0032] Furthermore, in step 1, calcium oxide, basic alumina, calcium formate, calcium silicate hydrate, carboxyl cellulose and solid polycarboxylate water reducer are all in powder form with a purity greater than 99%.
[0033] Furthermore, in step 2, the purity of polyaluminum sulfate, magnesium sulfate, disodium ethylenediaminetetraacetate and borax is greater than 99% and they are in powder form.
[0034] Furthermore, in step 2, the defoaming agent is a solid silicone defoaming agent with a purity of 99%.
[0035] Furthermore, in step 3, the particle size of the ultrafine fly ash is 0.4-0.6 μm, the loss on ignition is no more than 3.2%, the water requirement is no more than 91%, the water content is no more than 0.2%, and the activity index is 85%-90%.
[0036] Furthermore, in step 3, the purity of ultrafine silicon dioxide, ultrafine hydroxyapatite, ultrafine zinc sulfate and ultrafine boron nitride is greater than 99%, and the particle size is 1-5 μm.
[0037] Furthermore, in step 3, the particle size of nano titanium dioxide is 30-50 nm.
[0038] Furthermore, in step 4, the activator is 6 to 9 parts of aluminum carbonate powder with a purity of 98%.
[0039] The preparation method of the present invention adopts a mixed compounding technology, and the selected materials are scientifically and reasonably proportioned, and the required plugging material can be prepared without heating or a long chemical reaction. This preparation method is not only simple and easy to implement, but also greatly reduces energy consumption, which conforms to the concept of green environmental protection. At the same time, the packaging, transportation and storage of the preparation method are relatively simple and convenient, which reduces the logistics cost and storage difficulty, so that the material can be more widely used in practical engineering.
[0040] The quick-setting high-strength expansive leak crack plugging material prepared by the present invention has an initial setting time of 2 to 3 minutes and a final setting time of 4 to 6 minutes. The quick-setting high-strength expansive leak crack plugging material has a uniform structure, strong shrinkage resistance, and obvious micro-expansion characteristics, so that it can maintain a stable shape during the curing process and is not prone to cracks or deformation. The material has high early strength and good durability in the later stage, and can reach a higher strength in a short time to meet the requirements of the project for material performance. The initial setting time and final setting time of the material are relatively short, which greatly improves the construction efficiency and reduces the project cost. The strength in 1 hour is greater than 7MPa, the strength in 1 day is greater than 25MPa, and the strength in 28 days can be greater than 50MPa. The plugging and filling effects are obvious, providing reliable protection for the project.
[0041] The quick-setting high-strength expansion type leakage crack plugging material prepared by the present invention can be used in water vapor leakage, gap plugging and gap filling and repairing in coal mines, tunnels and dams. It can effectively prevent the generation of water vapor leakage cracks and improve the safety and durability of the project. The dense microstructure and the characteristics of anti-shrinkage and micro-expansion make the plugged structure more stable and reliable and not easily affected by the external environment. It is convenient to construct, can be quickly solidified and formed, greatly shortens the construction period, and reduces the project cost.
[0042] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all the embodiments. The components of the embodiments of the present invention generally described and shown here can be arranged and designed by various different configurations. Therefore, the following detailed description of the embodiments of the present invention is not intended to limit the scope of the claimed invention, but merely represents the selected embodiments of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work belong to the scope of protection of the present invention.
[0043] Example 1 A method for preparing a quick-setting high-strength expansion type leakage crack plugging material comprises the following steps: Step 1: 85 parts of ordinary Portland cement P·O 42.5, 45 parts of desulfurized gypsum, 20 parts of calcium oxide, 15 parts of basic alumina, 10 parts of calcium formate, 10 parts of hydrated calcium silicate, 0.1 parts of carboxyl cellulose, and 1.5 parts of solid polycarboxylate water reducer are mixed uniformly according to the weight ratio to obtain component A; Step 2: Evenly mix 40 parts of polyaluminium sulfate, 10 parts of magnesium sulfate, 0.5 parts of disodium ethylenediaminetetraacetate, 1 part of borax and 0.1 parts of defoamer according to weight proportions to obtain component B; Step 3, according to the mass parts, 40 parts of ultrafine fly ash, 30 parts of ultrafine silicon dioxide, 25 parts of ultrafine hydroxyapatite, 10 parts of ultrafine zinc sulfate, 5 parts of nano titanium dioxide and 10 parts of ultrafine boron nitride are mixed uniformly to obtain component C; Step 4: Add 75 parts of water to 186.6 parts of A, stir evenly to obtain component A slurry; add 21 parts of water to 51.6 parts of component B, stir evenly to obtain component B slurry; add 48 parts of water to 120 parts of component C, stir evenly to obtain component C slurry. Mix component A slurry, component B slurry and component C slurry evenly, add 6 parts of aluminum carbonate powder activator, stir evenly, and obtain a fast-setting high-strength expansion type leakage crack plugging material, which is immediately injected into the leakage and gaps that need to be plugged.
[0044] Example 2 A method for preparing a quick-setting high-strength expansion type leakage crack plugging material comprises the following steps: Step 1: 87 parts of ordinary Portland cement P·O 42.5, 47 parts of desulfurized gypsum, 23 parts of calcium oxide, 17 parts of basic alumina, 11 parts of calcium formate, 12 parts of hydrated calcium silicate, 0.15 parts of carboxyl cellulose, and 1.7 parts of solid polycarboxylate water reducer are mixed uniformly according to the weight ratio to obtain component A; Step 2: Mix 43 parts of polyaluminium sulfate, 11 parts of magnesium sulfate, 0.52 parts of disodium ethylenediaminetetraacetate, 1.5 parts of borax and 0.15 parts of defoamer in proportion by mass to obtain component B; Step 3, according to the mass parts, 42 parts of ultrafine fly ash, 31 parts of ultrafine silicon dioxide, 27 parts of ultrafine hydroxyapatite, 11 parts of ultrafine zinc sulfate, 6 parts of nano titanium dioxide and 12 parts of ultrafine boron nitride are mixed uniformly to obtain component C; Step 4: Add 80 parts of water to 198.85 parts of A, stir evenly to obtain component A slurry; add 23 parts of water to 56.17 parts of component B, stir evenly to obtain component B slurry; add 51 parts of water to 129 parts of component C, stir evenly to obtain component C slurry. Mix component A slurry, component B slurry and component C slurry evenly, add 7 parts of aluminum carbonate powder activator, stir evenly, and obtain a fast-setting high-strength expansion type leakage crack plugging material, which is immediately injected into the leakage and gaps that need to be plugged.
[0045] Example 3 A method for preparing a quick-setting high-strength expansion type leakage crack plugging material comprises the following steps: Step 1: According to the mass ratio, 90 parts of ordinary Portland cement P·O 42.5, 50 parts of desulfurized gypsum, 25 parts of calcium oxide, 20 parts of basic alumina, 13 parts of calcium formate, 13 parts of hydrated calcium silicate, 0.2 parts of carboxyl cellulose, and 2.0 parts of solid polycarboxylate water reducer are mixed uniformly to obtain component A; Step 2: Evenly mix 45 parts of polyaluminium sulfate, 13 parts of magnesium sulfate, 0.55 parts of disodium ethylenediaminetetraacetate, 2.5 parts of borax and 0.25 parts of defoamer according to weight fractions to obtain component B; Step 3, according to the mass parts, 45 parts of ultrafine fly ash, 33 parts of ultrafine silicon dioxide, 28 parts of ultrafine hydroxyapatite, 13 parts of ultrafine zinc sulfate, 7 parts of nano titanium dioxide and 13 parts of ultrafine boron nitride are mixed uniformly to obtain component C; Step 4: Add 85 parts of water to 213.2 parts of A, stir evenly to obtain component A slurry; add 25 parts of water to 61.3 parts of component B, stir evenly to obtain component B slurry; add 55 parts of water to 139 parts of component C, stir evenly to obtain component C slurry. Mix component A slurry, component B slurry and component C slurry evenly, add 7.5 parts of aluminum carbonate powder activator, stir evenly, and obtain a fast-setting high-strength expansion type leakage crack plugging material, which is immediately injected into the leakage and gaps that need to be plugged.
[0046] Example 4 A method for preparing a quick-setting high-strength expansion type leakage crack plugging material comprises the following steps: Step 1: According to the mass fraction, 92 parts of ordinary Portland cement P·O 42.5, 53 parts of desulfurized gypsum, 27 parts of calcium oxide, 23 parts of basic alumina, 14 parts of calcium formate, 14 parts of hydrated calcium silicate, 0.25 parts of carboxyl cellulose, and 2.3 parts of solid polycarboxylate water reducer are mixed uniformly to obtain component A; Step 2: Evenly mix 47 parts of polyaluminium sulfate, 14 parts of magnesium sulfate, 0.57 parts of disodium ethylenediaminetetraacetate, 2.5 parts of borax and 0.25 parts of defoamer according to weight fractions to obtain component B; Step 3, according to the mass parts, 47 parts of ultrafine fly ash, 34 parts of ultrafine silicon dioxide, 29 parts of ultrafine hydroxyapatite, 14 parts of ultrafine zinc sulfate, 7.5 parts of nano titanium dioxide and 14 parts of ultrafine boron nitride are mixed uniformly to obtain component C; Step 4: Add 90 parts of water to 225.55 parts of A, stir evenly to obtain component A slurry; add 26 parts of water to 64.32 parts of component B, stir evenly to obtain component B slurry; add 58 parts of water to 145.5 parts of component C, stir evenly to obtain component C slurry. Mix component A slurry, component B slurry and component C slurry evenly, add 8 parts of aluminum carbonate powder activator, stir evenly, and obtain a fast-setting high-strength expansion type leakage crack plugging material, which is immediately injected into the leakage and gaps that need to be plugged.
[0047] Example 5 A method for preparing a quick-setting high-strength expansion type leakage crack plugging material comprises the following steps: Step 1: 95 parts of ordinary Portland cement P·O 42.5, 55 parts of desulfurized gypsum, 30 parts of calcium oxide, 25 parts of basic alumina, 15 parts of calcium formate, 15 parts of hydrated calcium silicate, 0.3 parts of carboxyl cellulose, and 2.5 parts of solid polycarboxylate water reducer are mixed uniformly according to the weight ratio to obtain component A; Step 2: Mix 50 parts of polyaluminium sulfate, 15 parts of magnesium sulfate, 0.6 parts of disodium ethylenediaminetetraacetate, 3 parts of borax and 0.3 parts of defoamer in proportion by mass to obtain component B; Step 3, according to the mass parts, 50 parts of ultrafine fly ash, 35 parts of ultrafine silicon dioxide, 30 parts of ultrafine hydroxyapatite, 15 parts of ultrafine zinc sulfate, 8 parts of nano titanium dioxide and 15 parts of ultrafine boron nitride are mixed uniformly to obtain component C; Step 4: Add 95 parts of water to 237.8 parts of A, stir evenly to obtain component A slurry; add 28 parts of water to 68.9 parts of component B, stir evenly to obtain component B slurry; add 61.2 parts of water to 153 parts of component C, stir evenly to obtain component C slurry. Mix component A slurry, component B slurry and component C slurry evenly, add 9 parts of aluminum carbonate powder activator, stir evenly, and obtain a fast-setting high-strength expansion type leakage crack plugging material, which is immediately injected into the leakage and gaps that need to be plugged.
[0048] The fast-setting, high-strength, expansive leak crack plugging material prepared in Examples 1 to 5 is not limited to plugging water seepage, repairing cracks, and filling voids in coal mines. It can also be used to repair cracks in buildings, roads, and bridges, and can also be used as a jet flocculation reinforcement material for tunnels and goafs.
[0049] Refer to Table 1 for a performance comparison of the quick-setting high-strength expansive leakage crack plugging materials prepared in Examples 1 to 5 of the present invention. In order to facilitate the comparison of the effects of different material ratios on the performance of the samples, the quick-setting high-strength expansive leakage crack plugging materials prepared in Examples 1 to 5 were tested for performance in accordance with GB / T17671-2021 "Test Method for Strength of Cement Mortar" and GB / T50082-2023 "Standard for Test Method for Long-term Performance and Durability of Ordinary Concrete". The results are shown in Table 1. It can be seen from Table 1 that a quick-setting high-strength expansive leakage crack plugging material prepared in Examples 1 to 5 has excellent mechanical properties and durability, which are specifically manifested in: 1) 2 to 3 min initial setting, 4 to 6 min final setting, and 1 h compressive strength can reach 7.55 to 7.93 MPa; 1 day compressive strength reaches 26.54 to 31.52 MPa; It shows that it has the characteristics of fast setting speed and high early strength, which meets the performance requirements as a water gushing, water permeability and gas plugging material. 2) The compressive strength after 28 days reached 53.46~56.62MPa, indicating that the plugging material has a high strength. The compressive strength after 90 days reached 58.81~63.68 MPa, indicating that the plugging material has a good subsequent reinforcement effect. 3) The results of the 28-day freeze-thaw experiment and the anti-seepage test show that the plugging material has good durability, indicating that it has good anti-freeze performance and is more durable. 4) The carbonization resistance depth is 0.1~0.2 mm, which has good durability; 6) The volume shrinkage rate after 28 days is 0.1%~0.11%, indicating that it has good volume stability. 5) The results of the 28-day and 90-day shrinkage tests show that the plugging material has a good anti-shrinkage and micro-expansion effect. The quick-setting high-strength expansion type leakage crack plugging material prepared in Examples 1 to 5 has excellent working performance, volume stability and durability, and is suitable for making different types of cement-based composite parts.
[0050] Table 1 Performance comparison of the fast-setting high-strength expansion type leakage crack plugging materials prepared in Examples 1 to 5
[0051] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a rapid-setting high-strength expansion type leakage crack plugging material, characterized in that: The following steps are involved: Step 1, mixing cement, desulfurized gypsum, calcium oxide, basic alumina, calcium formate, hydrated calcium silicate, carboxyl cellulose and solid polycarboxylate water reducer to obtain component A; Step 2, mixing polyaluminium sulfate, magnesium sulfate, disodium ethylenediaminetetraacetate, borax and a defoamer to obtain component B; Step 3, mixing ultrafine fly ash, ultrafine silicon dioxide, ultrafine hydroxyapatite, ultrafine zinc sulfate, nano titanium dioxide and ultrafine boron nitride to obtain component C; Step 4, mix component A with water, stir evenly to obtain component A slurry; mix component B with water, stir evenly to obtain component B slurry; mix component C with water, stir evenly to obtain component C slurry; mix component A slurry, component B slurry and component C slurry evenly, then add an activator, stir evenly, and obtain a fast-setting high-strength expansion type leakage crack plugging material.
2. The method for preparing the rapid-setting high-strength expansive leakage crack plugging material according to claim 1, characterized in that: In step 4, the mass ratio of component A, component B, component C and activator is (186.6-237.8): (51.6-68.9): (120-153): (6-9); According to the mass percentage, the component A slurry is prepared by adding 75-95 parts of water to 186.6-237.8 parts of component A and stirring evenly; the component B slurry is prepared by adding 21-28 parts of water to 51.6-68.9 parts of component B and stirring evenly; the component C slurry is prepared by adding 48-61.2 parts of water to 120-153 parts of component C and stirring evenly; The activator is aluminum carbonate powder with a purity of 98%.
3. The method for preparing the rapid-setting high-strength expansion type leakage crack plugging material according to claim 1, characterized in that: In step 1, the mass ratio of the cement, desulfurized gypsum, calcium oxide, alkaline alumina, calcium formate, hydrated calcium silicate, carboxyl cellulose and solid polycarboxylate water reducer is (85-95): (45-55): (20-30): (15-25): (10-15): (10-15): (0.1-0.3): (1.5-2.5); In step 2, the mass ratio of the polyaluminium sulfate, magnesium sulfate, disodium ethylenediaminetetraacetate, borax and defoaming agent is (40-50): (10-15): (0.5-0.6): (1-3): (0.1-0.3); In step 3, the mass ratio of the ultrafine fly ash, ultrafine silicon dioxide, ultrafine hydroxyapatite, ultrafine zinc sulfate, nano titanium dioxide and ultrafine boron nitride is (40-50): (30-35): (25-30): (10-15): (5-8): (10-15).
4. The method for preparing the rapid-setting high-strength expansive leakage crack plugging material according to claim 1, characterized in that: In step 1, the cement is ordinary Portland cement P·O 42.5; the main component of the desulfurized gypsum is CaSO4·2H2O, the content of which is 93%, and the average particle size is 50 μm.
5. The method for preparing the rapid-setting high-strength expansion type leakage crack plugging material according to claim 1, characterized in that: In step 1, the calcium oxide, basic alumina, calcium formate, hydrated calcium silicate, carboxyl cellulose and solid polycarboxylate water reducer are all powdered materials with a purity greater than 99%.
6. The method for preparing the rapid-setting high-strength expansive leakage crack plugging material according to claim 1, characterized in that: In step 2, the polyaluminum sulfate, magnesium sulfate, disodium ethylenediaminetetraacetate and borax are all powdered materials with a purity greater than 98%; the defoaming agent is a solid silicone defoaming agent with a purity of 99%.
7. The method for preparing the rapid-setting high-strength expansive leakage crack plugging material according to claim 1, characterized in that: In step 3, the particle size of the ultrafine fly ash is 0.4-0.6 μm, the loss on ignition is not more than 3.2%, the water requirement is not more than 91%, the water content is not more than 0.2%, and the activity index is 85%-90%.
8. The method for preparing the rapid-setting high-strength expansion type leakage crack plugging material according to claim 1, characterized in that: In step 3, the purity of the ultrafine silicon dioxide, ultrafine hydroxyapatite, ultrafine zinc sulfate and ultrafine boron nitride is greater than 99%, and the particle size is 1-5 μm; the particle size of the nano titanium dioxide is 30-50 nm.
9. A fast-setting high-strength expansion type leakage crack plugging material, characterized in that: The quick-setting high-strength expansive leakage crack plugging material is prepared by the preparation method of any one of claims 1 to 8; the initial setting time of the quick-setting high-strength expansive leakage crack plugging material is 2 to 3 minutes; the final setting time is 4 to 6 minutes; the 1h compressive strength is 7.55 to 7.93 MPa; the 1-day compressive strength is 26.54 to 31.52 MPa; the 28-day compressive strength is 53.46 to 56.62 MPa; the 90-day compressive strength is 58.81 to 63.68 MPa; the 28-day carbonization resistance depth is 0.1 to 0.2 mm; and the 28-day volume shrinkage rate is 0.1% to 0.11%.
10. Application of the quick-setting high-strength expansive leakage crack plugging material obtained by the preparation method of the quick-setting high-strength expansive leakage crack plugging material according to any one of claims 1 to 8 in water and gas leakage, gap plugging and void filling and repair in coal mines, tunnels and dams.
Citation Information
Patent Citations
Rapid-hardening micro-expansion hole sealing material
CN103193449A
Alkali-free high-strength concrete flash setting admixture
CN105753364A
Early-strength setting accelerator, high temperature-resistant anti-cracking waterproof plugging material and preparation method and construction material of high temperature-resistant anti-cracking waterproof plugging material
CN110395931A
Ultrafine solid waste-based grouting material and preparation method thereof
CN112500056A
Mortar composition for repairing and reinforcing concrete structure, and method of repairing and reinforcing concrete structure using the same
KR101893060B1
Cited By
Organic in-situ polymerization modified cement-based grouting material for plugging leakage / water burst channel and grouting method of organic in-situ polymerization modified cement-based grouting material
CN121672984A
Concrete crack repair agent for seepage conditions and preparation method and application thereof
CN122520853A